Rice price volatility and market integration between Indonesia and Thailand under COVID-19 - ANGKY DWI SEFFYANTO; YUSMAN SYAUKAT; SRI HARTOJO; AHMAD FAROBY FALATEHAN (Asian Journal of Agriculture, 2026)
Abstract. Seffyanto AD, Syaukat Y, Hartojo S, Falatehan AF. 2026. Rice price volatility and market integration between Indonesia and Thailand under COVID-19. Asian J Agric 10 (2): g100206. https://doi.org/10.13057/asianjagric/g100206. Rice price stability is central to Indonesian food security because rice remains a major component of household expenditure and consumer price sensitivity. Although Indonesia is a major rice producer, domestic prices remain linked to international markets through imports, particularly from Thailand. This study examines whether the COVID-19 crisis disrupted Indonesia-Thailand rice market integration or temporarily weakened short-run price transmission through domestic stabilization policies. Using weekly data from January 2018 to December 2024 (N = 336), we apply Johansen cointegration, a Vector Error Correction Model with regime-shift dummies, Granger causality tests, and GARCH modeling. The Johansen test confirmed one stable long-run cointegrating relationship, estimated as PTH = 0.7976PID + 0.2336. VECM results showed gradual equilibrium adjustment, with an estimated half-life of approximately 25-26 weeks. Under normal conditions, Thai FOB prices were strongly transmitted to Indonesian domestic prices, with a coefficient of 1.0370. During the COVID-19 period, the interaction coefficient of -1.0189 reduced net short-run transmission to 0.0181, indicating near-zero pass-through during the crisis. Granger causality tests showed weak predictive influence from Thailand to Indonesia (p = 0.0798) and stronger predictive influence from Indonesia to Thailand (p = 0.0013). GARCH results showed divergent volatility responses, with Indonesian volatility slightly declining from 1.1164% to 1.0982%, while Thai volatility increased from 1.2617% to 1.8470. These findings indicate that COVID-19 weakened short-run price transmission but did not break long-run market integration. The results are consistent with the buffering role of Indonesian stabilization policies, although causal interpretation remains limited by the observational design.